EFL STUDENTS’ PERCEPTION TOWARDS THE USE OF ENGLISH SONGS AS LISTENING LEARNING MEDIA - Putri, Brigita Griska; Degeng, Putu Dian Danayanti; Isnaini, Mohammad Hasbullah (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2022)
This article investigates students' perceptions and challenges of using English songs as their listening learning media. This study used a mixed method, namely the explanatory sequential mixed method, with two instruments: questionnaire and interview. The data in this study were obtained from 49 SMK Negeri 2 Batu students. This study reveals that students perceive the use of songs as media for listening learning. There are 87.8% of students use songs for listening practices, and 91.8% agree that they are more comfortable using songs to learn listening than other media. Besides, there were obstacles in the form of students' difficulties in quickly recognizing the words spoken in a song with a fast tempo. The overall findings of this study are that English songs are suitable for use as listening learning media in and outside the classroom by considering the selection of songs according to the level of English and student preferences.